Karakteristik Struktur, Fungsionalitas dan Sifat Fisis Silika Aspal Dengan Perbandingan 65%: 35% - Novendra Prisbana Tarigan; Simon Sembiring; Leni Rumiyanti (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Synthesis and characterization of silica composites of rice husk and asphalt with a ratio of 65%: 35% has been carried out. This study aims to see the characteristics of the structure, functionality and physical properties, namely moisture content and thickness development of the sample. The synthesis of silica from rice husks was carried out by the sol-gel method. Based on the research that has been done, the XRD characterization results obtained in the sample have the structure of silica and amorphous carbon, then the results of FTIR characterization show the Si - OH functional group (silanol) occurs at wave number 3528, metal hydroxide Si - OH (silanol) is oxidized to Si - O - Si and Si - O were formed at wave numbers 1081 cm-1, 792 cm-1 and 471 cm-1 and the formation of the C - H stretching functional group occurred at wave numbers 2932 cm-1, 2853 cm-1. Then test the physical properties of water content of 5.813% with a change in thickness development of 9.753%. So it can be concluded that the addition of bitumen to the silica sample changes the phase structure of the sample and changes the original spectrum of rice husk silica.